Motivational Factors Influencing English Learning Among Students at UniversitÃ© Catholique De Bukavu: A Self-Determination Perspective - Baha, Laurent Mutegheki (Journal of English Education Program, 2025)
Despite the importance of English proficiency for global opportunities, students at the UniversitÃ© Catholique de Bukavu face unique challenges in language learning motivation. This study addresses this research gap by examining motivational factors influencing English learning among these students through the lens of Self-Determination Theory (SDT). Using a descriptive quantitative design, 100 randomly selected first-year students from diverse faculty completed a questionnaire adapted from the Attitude/Motivation Test Battery (AMTB). The findings revealed that career prospects and effective communication with diverse groups serve as primary motivators, while moderate levels of perceived autonomy and competence have been reported. Sociocultural and economic challenges unique to Bukavu, such as limited exposure to English speakers and scarce learning resources, were found to influence these motivational factors. The results emphasize the need for educational strategies that increase autonomy, foster competence and support self-directed learning. These insights contribute to understanding how motivational dynamics interact with socio-cultural factors in non-English-speaking regions and offer practical recommendations for enhancing English language education